Efisiensi Kinerja dan Hasil Panen Teh Menggunakan Gunting dan Mesin pada Beragam Kemiringan Lahan - Ahmad Thoriq; Krawali Sita (Jurnal Tanaman Industri dan Penyegar, 2021)
Tea leaf plucking is an important activity that can determine the quantity and quality of tea production. Tea plantations characteristically have variations of slopes that affect the performance of the picking process. This study aimed to analyze the performance efficiency of tea plucking activities using plucking machines and scissors. Field data were collected from several blocks in the South Gambung and North Gambung afdeling. Data collected consisted of the elevation of the place, the slope of the land, the plucking area, plucking time, the number of pluckers, the plots length of the plucking activity, the width of the plots, and the harvested tea's weight. The data collected were processed into field capacity and tea plucking performance efficiency, which were then analyzed descriptively. Results showed that the slope of the land has an effect on work efficiency of 3.00%-8.68%. The effective and theoretical field capacity of tea plucking machines is 0.14 hectares per hour and 0.20 hectares per hour, respectively, while the scissors is 0.015 hectares per hour and 0.020 hectares per hour. The quality of tea harvested with machines that meet the requirements is 44.10%, better than scissors harvested, which is only 28.09%.